A self‐salt‐cleaning architecture in cold vapor generation system for hypersaline brines. Issue 2 (10th January 2022) - Kunjaram, Uma Pratheebha Umaiya; Song, Haomin; Liu, Youhai; Booker, Brandon K.; Cooke, Timothy J.; Gan, Qiaoqiang
Abstract: Desalination of seawater with zero‐liquid discharge is a major challenge. Here we developed a three‐dimensional "umbrella" architecture to evaporate hypersaline brines of up to 20 wt% using solar‐driven interfacial evaporation. By controlling the water pathway and the thickness of the evaporator films to manipulate the salt capacitance of the system, a stable evaporation rate of >2.6 kg m −2  h −1 was achieved over 4‐day operation in the laboratory environment with minimized salt accumulation on evaporation surfaces. By placing the system in an outdoor environment with natural wind, the peak evaporation rate was improved to 9.05 kg m −2  h −1 . After a 4‐day outdoor test, the total evaporated water by the umbrella system was 3.7× more than the natural evaporation from a bulk water surface under identical environmental conditions. The predesigned water flow also controlled the local salt accumulation, resulting in easier salt removing and collection, which is highly desired for accelerated salt mining applications. Abstract : A self‐salt‐cleaning design is proposed for maintenance‐free solar‐ and wind‐driven interfacial evaporation. The large surface area of the architecture results in high evaporation rates. Due to the water transportation and the salt capacitance engineering, the salt accumulation and fouling issues are minimized. The desalination of hypersaline water reveals the potential for fresh‐water production and high value salt mining applications with zero‐liquid discharge.